2017
DOI: 10.1016/j.bcp.2017.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Spatial encryption of G protein-coupled receptor signaling in endosomes; Mechanisms and applications

Abstract: Within any cellular signaling system membrane trafficking is a critical mechanism for cells to translate complex networks into specific downstream responses, including the signal pathways activated by the superfamily of G protein-coupled receptors (GPCRs). Classically, membrane trafficking is viewed as a mechanism to regulate ligand sensitivity of a target tissue by controlling the level of surface receptors. Recent studies, however, have not only highlighted that GPCR trafficking is a tightly regulated proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…There has been an increasing number of reports that GPCRs can continue, or reactivate, G-protein signaling from endosomes ( Sposini and Hanyaloglu, 2017 , Irannejad et al., 2015 ), although GPCR/G-protein signaling from endosomes distinct from the EE has not previously been demonstrated. Interestingly, sustained cAMP signaling from the mouse LHR in the ovary is purportedly important for maintaining meiotic arrest in oocytes ( Lyga et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been an increasing number of reports that GPCRs can continue, or reactivate, G-protein signaling from endosomes ( Sposini and Hanyaloglu, 2017 , Irannejad et al., 2015 ), although GPCR/G-protein signaling from endosomes distinct from the EE has not previously been demonstrated. Interestingly, sustained cAMP signaling from the mouse LHR in the ovary is purportedly important for maintaining meiotic arrest in oocytes ( Lyga et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…While under pathophysiological conditions, this can lead to perturbed GPCR signaling and disease ( Sobolik et al., 2014 , Barak et al., 2001 ). Recent studies, however, have demonstrated that G-protein signaling can continue, or be reactivated, following receptor internalization (reviewed in Sposini and Hanyaloglu, 2017 , Irannejad et al., 2015 ), highlighting a key functional role of the endocytic system in GPCR activation. However, how membrane trafficking spatially decodes complex signaling pathways remains a fundamental outstanding biological question.…”
Section: Introductionmentioning
confidence: 99%
“…GPCR signaling from endosomes is now well documented for many receptors, and it has been discussed in several recent reviews [6,7] but its role in neuronal function is just starting to be addressed. Endosomal signaling was first described using MAPK activation as an output for the protease activated receptor PAR2 [30] and for the angiotensin receptor ATR1 [31].…”
Section: Spatial Encoding At Endosomesmentioning
confidence: 99%
“…These trafficking steps were primarily viewed as mechanisms to remove receptors from or add GPCRs to the cell surface, thereby regulating receptor access to extracellular signals and modulating cell sensitivity to signals [5]. While this is still valid, several GPCRs, including canonical receptors previously thought to signal primarily from the surface, are now known to signal from multiple intracellular compartments [6][7][8]. The downstream consequences of signaling (e.g., the genes that are activated) for any given receptor can differ based simply on the compartment in which…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, APPL1 is not required for GPCR localization to the VEE but is essential for LHR and FSHR recycling (Figure 2C ). Interestingly, it is the receptor's own cAMP/PKA signaling that drives this APPL1-dependent recycling ( 60 ). The mechanism underlying this requirement is that LH-mediated PKA activation must phosphorylate APPL1 at serine 410 for the receptor to recycle back to the plasma membrane.…”
Section: Post-endocytic Sorting and Endosomal Signaling Of Fshr From mentioning
confidence: 99%